2017
DOI: 10.3389/fpls.2017.00207
|View full text |Cite
|
Sign up to set email alerts
|

Glyphosate-Dependent Inhibition of Photosynthesis in Willow

Abstract: We studied the physiological mechanisms involved in the deleterious effects of a glyphosate-based herbicide (Factor® 540) on photosynthesis and related physiological processes of willow (Salix miyabeana cultivar SX64) plants. Sixty-day-old plants grown under greenhouse conditions were sprayed with different rates (0, 1.4, 2.1, and 2.8 kg a.e ha-1) of the commercial glyphosate formulated salt Factor® 540. Evaluations were performed at 0, 6, 24, 48, and 72 h after herbicide exposure. We established that the herb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 71 publications
5
59
0
1
Order By: Relevance
“…It has also been reported that glyphosate has detrimental effects on photosynthetic processes that could be directly or indirectly linked to glyphosate-induced reductions of plastoquinone (PQ) biosynthesis (Cobb and Reade, 2010;Gomes et al, 2017b) and chlorophyll concentrations . Reduction of PQ and chlorophyll contents will directly affect the chloroplast electron transport rate (ETR).…”
Section: Case Of Glyphosate and Temperaturementioning
confidence: 99%
“…It has also been reported that glyphosate has detrimental effects on photosynthetic processes that could be directly or indirectly linked to glyphosate-induced reductions of plastoquinone (PQ) biosynthesis (Cobb and Reade, 2010;Gomes et al, 2017b) and chlorophyll concentrations . Reduction of PQ and chlorophyll contents will directly affect the chloroplast electron transport rate (ETR).…”
Section: Case Of Glyphosate and Temperaturementioning
confidence: 99%
“…Photosynthesis has been shown to be impaired by glyphosate-based herbicides within wide ranges of concentrations, including in cordgrass Spartina densiflora from spray application at concentrations of 720-7200 g ha −1 [37], to direct contact of 10-80 mg L −1 in Anabaena fertilissima [38]. In both cases, there was inhibition of CO 2 assimilation and depletion of intermediates from the photosynthetic carbon reduction cycle due to deregulation of the shikimate pathway [39,40]. In such scenarios, non-invasive high-throughput bio-optical screening tools, such as Pulse Amplitude Modulated (PAM) fluorometry, emerge as invaluable techniques to evaluate ecotoxicity in photosynthetic organisms [12,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Glyphosate inhibits EPSPS, disrupting the biosynthesis of phenylalanine, tyrosine, tryptophan and others secondary aromatic products 10 . This is due to the complex effects caused by glyphosate on the shikimate pathway, the photosynthetic processes and the oxidative events of plants 11 , triggering the expression of other chloroplast enzymes 12 . Recently, the expression of the phosphofructokinase (PFK: EC 2.7.1.11) enzyme has been strongly associated with EPSPS expression 13 .…”
Section: Introductionmentioning
confidence: 99%